Consumption of High‐Oleic Soybean Oil Improves Lipid and Lipoprotein Profile in Humans Compared to a Palm Oil Blend: A Randomized Controlled Trial. Issue 3 (17th February 2021) - Baer, David J.; Henderson, Theresa; Gebauer, Sarah K.
Abstract: Partially hydrogenated oils (PHO) have been removed from the food supply due to adverse effects on risk for coronary heart disease (CHD). High‐oleic soybean oils (HOSBO) are alternatives that provide functionality for different food applications. The objective of this study was to determine how consumption of diets containing HOSBO compared to other alternative oils, with similar functional properties, modifies LDL cholesterol (LDLc) and other risk factors and biomarkers of CHD. A triple‐blind, crossover, randomized controlled trial was conducted in humans (n = 60) with four highly‐controlled diets containing (1) HOSBO, (2) 80:20 blend of HOSBO and fully hydrogenated soybean oil (HOSBO+FHSBO), (3) soybean oil (SBO), and (4) 50:50 blend of palm oil and palm kernel oil (PO + PKO). Before and after 29 days of feeding, lipids/lipoproteins, blood pressure, body composition, and markers of inflammation, oxidation, and hemostasis were measured. LDLc, apolipoprotein B (apoB), NonHDL‐cholesterol (HDLc), ratios of total cholesterol (TC)‐to‐HDLc and LDLc‐to‐HDL cholesterol, and LDL particle number and small LDL particles concentration were lower after HOSBO and HOSBO+FHSBO compared to PO (specific comparisons p  < 0.05). Other than TC:HDL, there were no differences in lipid/lipoprotein markers when comparing HOSBO+FHSBO with HOSBO. LDLc and apoB were higher after HOSBO compared to SBO ( p  < 0.05). PO + PKO increased HDLc ( p  < 0.001) and apolipoprotein AI ( p  < 0.03) compared to HOSBO and HOSBO+FHSBO. With the exception of lipid hydroperoxides, dietary treatments did not affect other CHD markers. HOSBO, and blends thereof, is a PHO replacement that results in more favorable lipid/lipoprotein profiles compared to PO + PKO (an alternative fat with similar functional properties).